La idea más maravillosa - Spires, Ashley, 1978- author, illustrator (Primera edición. Barcelona : Beascoa/Penguin Random House Grupo Editorial, 2017., 2017)
1 volume (unpaged) : color illustrations ; 23 cm
Translated from: The most magnificent thing.;Spanish.